Measurement of [upsilon] (1S) elliptic flow at forward rapidity in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Physical review letters, 2019)
The first measurement of the Υ(1S) elliptic flow coefficient (v2) is performed at forward rapidity (2.5<y<4) in Pb-Pb collisions at √sNN=5.02 TeV with the ALICE detector at the LHC. The results are obtained with the scalar product method and are reported as a function of transverse momentum (pT) up to 15 GeV/c in the 5%-60% centrality interval. The measured Υ(1S)v2 is consistent with 0 and with the small positive values predicted by transport models within uncertainties. The v2 coefficient in 2<pT<15 GeV/c is lower than that of inclusive J/ψ mesons in the same pT interval by 2.6 standard deviations. These results, combined with earlier suppression measurements, are in agreement with a scenario in which the Υ(1S) production in Pb-Pb collisions at LHC energies is dominated by dissociation limited to the early stage of the collision, whereas in the J/ψ case there is substantial experimental evidence of an additional regeneration component.